KEKUATAN DAN UMUR FATIK STRUKTUR PENOMPANG JAW CRUSHER DENGAN METODE ELEMEN HINGGA - Nurhayati; T R Wijaya (Jurnal Infrastruktur, 2019)
The structure would be work well accordance to its capacity and it has the static loadings that were under limit the yield strength of the material, can be subjected to failure during operations, and this is because the structure receives additional dynamic loads that occur repeatedly within a long period of time as known as cyclic loads or fatigue loads. The purpose of the fatigue analysis is to find out the working life of structure so, the structure can be planned to repair and strengthen without disturbing the operation process. In real operations, the structure support of jaw crusher receives fatigue load from the equipment which standing on it. Structure alaysed by used finite element method with the aim to get more accurate analysis results. The type of analysis used is constants amplitude events. Based on the analysis results obtained the life of the jaw crusher is for 67000 cycles or 8 months 28.